Telomeric gene deletion and intrachromosomal amplification in antimony‐resistant Leishmania. Issue 1 (6th March 2013) - Mukherjee, Angana; Boisvert, Sébastien; Monte‐Neto, Rubens Lima do; Coelho, Adriano C.; Raymond, Frederic; Mukhopadhyay, Rita; Corbeil, Jacques; Ouellette, Marc
Summary: Antimonials are still the mainstay of treatment against leishmaniasis but drug resistance is increasing. We carried out short read next‐generation sequencing (NGS) and comparative genomic hybridization (CGH) of three independent Leishmania major antimony‐resistant mutants. Copy number variations were consistently detected with both NGS and CGH. A major attribute of antimony resistance was a novel terminal deletion of variable length (67 kb to 204 kb) of the polyploid chromosome 31 in the three mutants. Terminal deletions in two mutants occurred at the level of inverted repeated sequences. The AQP1 gene coding for an aquaglyceroporin was part of the deleted region and its transfection into resistant mutants reverted resistance to SbIII. We also highlighted an intrachromosomal amplification of a subtelomeric locus on chromosome 34 in one mutant. This region encoded for ascorbate‐dependent peroxidase (APX) and glucose‐6‐phosphate dehydrogenase (G6PDH). Overexpression of these genes in revertant backgrounds demonstrated resistance to SbIII and protection from reactive oxygen species (ROS). Generation of a G6PDH null mutant in one revertant exhibited SbIII sensitivity and a decreased protection of ROS. Our genomic analyses and functional validation highlighted novel genomic rearrangements, functionally important resistant loci and the implication of new genes in antimony resistance in Leishmania .